Heavy metal pollution status in the sediment layer in World Heritage Site: Indian Sundarbans estuarine region - Chakraborty, Shankhadeep; Mitra, Abhijit (Vietnam Journal of Science and Technology, 2018)
Heavy metals have a great ecological significance due to their toxicity and accumulative behavior. The geoaccumulation index (Igeo) in 12 stations in the UNESCO declared World Heritage Site- Indian Sundarbans estuarine region (i.e Kakdwip, Harinbari, Chemaguri, Sagar South, Lothian island, Jambu island, Frasergunge, Gosaba, Chotomollakhali, Bali island, Sajnekhali and Bagmara) were calculated for the year 2016. The sediment pollution was investigated by following the concentration of 3 heavy metals namely copper, lead and cadmium. Atomic Absorption Spectrophotometer (AAS) was used for analysis. According to the geoaccumulation index (Igeo) the results of all the 10 stations were analyzed and discussed in details.